Formulation and Characterization of Nanoemulsion of Tread leave Ethanol Extract (Catharanthus roseus (L.) G. Don) as Antihyperglycemic - Mariadi; Prasetyo, Bayu Eko; Adela, Hanny; Wiladatika, Winda (Indonesian Journal of Pharmaceutical and Clinical Research, 2019)
Nanoemulsion technology has been widely developed and applied on natural extract to enhance bioavailability and drug effects. The tread plant (Catharanthus roseus (L.) G. Don) is commonly known in traditional medicine for lowering blood sugar levels. This study aimed to make and characterize nanoemulsion of tread leaf extract as antihyperglycemic using sesame oil and olive oil as carriers. Nanoemulsion formulations were made using ethanol extract of tread leaves, and additives such as Tween 80, isopropyl myristate in varying ratios and some of vegetable oils. The nanoemulsion was physically evaluated tests including the pH, the type of emulsion, homogeneity and size distribution which measured by the Particle Size Analyzer (PSA). Antihyperglycemic testing was carried out on 4 groups of male mice (5 mice/ group) induced with glucose and treated with extract, nanoemulsion, and distilled water. The results showed that the nanoemulsion preparation had a pH of 6.4 to 6.5; o/w type of emulsion and it was stable on storage for 1 month. The particle size distribution of the nanoemulsion was 85.8% with size <500 nm. Nanoemulsion could reduce the blood glucose levels in mice to normal level after 60 minutes. It also showed the decreae for 43-46% of the blood glucose level after 2 hours. The Nanoemulsion of tread leaf extract has a faster ability and a greater percentage in reducing blood glucose levels compared to extract and control. Keywords: Nanoemulsion, Catharanthus roseus, sesame oil, olive oil, Antihyperglikemic